EFEKTIFITAS YOGA PRANAYAMA DAN AROMATERAPI TERHADAP PENINGKATAN KUALITAS TIDUR DAN KUALITAS HIDUP PASIEN KANKER - Widani, Ni Luh; Purnamasari, Ni Nyoman Indah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Cancer is cells that grow uncontrollably and include chronic diseases that cause physiological and psychological problems. The purpose of this research were determine of an effectiveness of yoga pranayama and aromatherapy to improve sleep quality and quality of life for cancer patients. The type of this study is an experimental with non equivalent control group pretest-posttest design, with 126 samples with purposive sample. Pittsburgh Sleep Quality Index (PSQI) used to evaluated sleep quality and Quality of Life Questionnaire (QLQ C30) to evaluatde quality if life. The result of this research using sample paired t-test there was a difference in sleep quality and quality of life before and after intervention yoga   and aromatherapy (p 0.00;<0,05);  by using one way ANOVA, there was different between three group and different improvement between intervention and control group (p<0,05  It?s concluded that yoga   and aromatherapy effective improve sleep quality and quality of life to cancer patients and the more effective in aromatherapy. The cancer patients are suggested to take yoga and aromatherapy as a complementary therapy to improve sleep quality and quality of life.